Precautionary Attachment of Digital Assets: A Comparative Study between the Saudi Enforcement Law and English Law - Yusra Jaber Al-Dhubyani; Al-Hanouf Abdulaziz Al-Sulami (International Journal of Law Research and Studies, 2025)
This study aims to clarify the concept and types of digital assets within a comparative analytical framework, enriched by an examination of a number of English judicial precedents specifically addressing the precautionary attachment of digital assets. The study begins by defining digital assets, their types, and their legal nature in this context. It then addresses the concept of precautionary attachment, its conditions, and its scope. Furthermore, the study examines the extent to which digital assets may be subject to precautionary attachment through an analysis of judicial precedents under English common law, while also highlighting key features of the Singaporean approach in this regard. This is intended to contribute to the Saudi legal framework in light of the absence of explicit legislative regulation of digital assets within the Saudi Enforcement Law. The study also seeks to clarify the extent of judicial authority in issuing precautionary judicial orders relating to digital assets, while highlighting the practical and legal challenges associated with their intangible nature and cross-border character.The study reaches several findings, most notably that the Saudi regulator has not yet provided an explicit statutory definition of digital assets in any of the applicable laws or regulations, nor has it permitted dealing in or trading such assets within the Kingdom, as confirmed by official statements issued by regulatory authorities. Nevertheless, in contrast, digital assets have occupied a significant place in comparative legal scholarship, particularly within comparative legal systems. Digital assets are defined as data recorded on the blockchain that confer specific rights such as ownership, access, representation, voting, or practical use. The scope of digital assets extends to include a wide range of digitally stored content and rights, including cryptocurrencies, non-fungible tokens (NFTs), and Bitcoin.The study also proposes several recommendations, most importantly that the Saudi regulator should introduce an explicit statutory provision defining digital assets within one of the applicable laws or regulations, whether within the framework of the Capital Market Law, commercial transaction laws, or monetary regulations. This would ensure clarity regarding the legal nature of such assets, define their scope, and enhance the ability to regulate and deal with them in accordance with statutory rules and specific controls. The study further recommends amending Article (24/3) of the Implementing Regulations of the Enforcement Law to expressly include digital assets among the assets subject to precautionary attachment. Following such amendment, the provision would read as follows: All assets of the debtor shall be subject to precautionary attachment, whether movable, immovable, or digital assets in all their forms.
Keywords: Precautionary Attachment; Precautionary Attachment of Digital Assets; Blockchain-Based Digital Assets; Saudi Enforcement Law Issued in 1433 AH; English Common Law; Precautionary Judicial Orders; Freezing Orders; Cryptocurrencies